DEFINING ASIAN LITERATURE (IN ENGLISH): A STUDY ON KAZUO ISHIGURO’S THE REMAINS OF THE DAY, HARUKI MURAKAMI’S NORWEGIAN WOOD AND DAVID MITCHELL’S NUMBER9DREAM - Ismiati .; Nunuk Tri Hapsari, S.S., M.Hum. (Conscientia, 2022)
Debating what works can be included in the study of Asian literature has given us difficult yet interesting discussion. This paper aims at comparing and contrasting the three literary works to propose what should be included in the consideration of which work should be included in the study of Asian literature. The three texts are selected as to meet the three differences: the first work is written by Asian writer and originally written in English; the second work is written by Asian writer but translated into English; and the third work is written by non-Asian writer but uses Asian setting. The methods applied in the research are the library research as the method for collecting the data, and the descriptive analytical method as the method of analyzing the data. Kazuo Ishiguro’s The Remains of the Day (1989) which has won the Man Booker Prize for Fiction tells a story of a very dedicated English buttler named Stevens. It does not present Japanese story nor setting. Haruki Murakami’s Norwegian Wood (1987) presents us Japanese story of Toru Watanabe and his love relationships with Naoko and Midori with the Japanese setting. David Mitchell’s Number9dream (2001) presents us the experience of Eiji Miyake’s search of his father in Japan. The considerations for a work to be eligible as part of Asian literature should first go with the story and the theme of the work, then with the original language of the novel and finally the background of the author. As a conclusion, among these three works, I propose that Haruki Murakami’s Norwegian Wood is best representing Japanese literature.